Detection of autoantibodies to heat shock protein 70 in the saliva and urine of normal individuals - Sitko, Krzysztof; Mantej, Jagoda; Bednarek, Marta; Tukaj, Stefan (Frontiers in Immunology, 2024)
Cells exposed to stressors of various origin activate protective mechanisms that include the expression of heat shock proteins (Hsps)/molecular chaperones belonging to several families. Well-characterized inducible Hsp70 is present in all human cell-types and biological fluids, including blood, urine, and saliva. The presence of anti-Hsp70 autoantibodies in the serum of healthy individuals has already been confirmed, and their elevated titers positively correlated with the severity of several pathological conditions. Here, we demonstrate, for the first time, that anti-Hsp70 autoantibodies are present in the saliva and urine of healthy individuals. Although the occurrence of anti-Hsp70 autoantibodies in the biological fluids of healthy individuals is intriguing, their physiological role is currently unknown. It is believed that antibodies reacting with self-molecules present in the serum of healthy individuals are part of natural autoantibody pool with multiple regulatory functions. On the other hand, some autoantibodies may be present before the onset of the disease and serve as specific predictive biomarkers. Therefore, we would like to initiate a discussion or future research direction on the use of anti-Hsp70 autoantibodies as a potential "biomarker" in the diagnosis or prediction of autoimmune diseases. Nevertheless, large scale comparative studies should be initiated, involving the collection and analysis of biological samples such as saliva or urine from patients suffering from autoimmune diseases or other inflammatory or neoplastic diseases, to determine whether the levels of anti-Hsp70 autoantibodies are indeed elevated and whether they correlate with the clinical picture of any disease or established biomarkers.